Energizing development finance? The benefits and risks of China's development finance in the global energy sector. (November 2018) - Gallagher, Kevin P.; Kamal, Rohini; Jin, Junda; Chen, Yanning; Ma, Xinyue
Abstract: This paper provides the first estimates of China's global developmental finance institutions in general and China's policy bank lending to foreign governments for energy in particular. According to the China Global Energy Finance database, between 2000 and 2017, China Development Bank (CDB) and China Export-Import Bank (CHEXIM) provided $225.75 billion in overseas energy development finance. We find that: China's 'policy banks' and funds have doubled the availability of global development finance –and hold more assets than the major Western-backed MDBs operating in developing countries. With the onset of a new family of funds and multilateral development banks co-financed by China, China is poised to be the largest development lender in the world as Western-backed MDBs appear stagnated in their ability to increase their capital bases. China's global energy portfolio is heavily exposed to country, macroeconomic, climate, and social risks, however. To mitigate such risks and meet the broader sustainable development challenge for the 21 st Century, China's development finance will need to shift the composition of its global energy lending in a significant manner. Highlights: China has doubled global development finance. Chinese energy finance is exposed to significant country and macroeconomic risk. Chinese development banks are heavily exposed to climate and social risk.